2016
DOI: 10.1175/jtech-d-15-0020.1
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Vertical Profiles—A New Way to Look at Polarimetric Radar Data

Abstract: A novel methodology is introduced for processing and presenting polarimetric data collected by weather surveillance radars. It involves azimuthal averaging of radar reflectivity Z, differential reflectivity ZDR, cross-correlation coefficient ρhv, and differential phase ΦDP at high antenna elevation, and presenting resulting quasi-vertical profiles (QVPs) in a height-versus-time format. Multiple examples of QVPs retrieved from the data collected by S-, C-, and X-band dual-polarization radars at elevations rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 13 publications
4
162
0
Order By: Relevance
“…However, this reduction is expected to be more intense for riming than for aggregation. Riming makes the ice particles more spherical leading to a lower Z DR by 0.1-0.3 dB (Ryzhkov et al, 2016). Thus, we speculate that riming causes the "sagging" effects of Z DR and ρ HV combined with relatively low Z DR above the ML around 12:00 and 13:00 UTC.…”
Section: Case 3: Riming/aggregation Processes Observed By Juxpolmentioning
confidence: 82%
See 2 more Smart Citations
“…However, this reduction is expected to be more intense for riming than for aggregation. Riming makes the ice particles more spherical leading to a lower Z DR by 0.1-0.3 dB (Ryzhkov et al, 2016). Thus, we speculate that riming causes the "sagging" effects of Z DR and ρ HV combined with relatively low Z DR above the ML around 12:00 and 13:00 UTC.…”
Section: Case 3: Riming/aggregation Processes Observed By Juxpolmentioning
confidence: 82%
“…Figure 13 shows so-called quasi-vertical profiles (QVPs) of Z H , Z DR , ρ HV and K DP based on JuXPol measurements at 18 • elevation angle between 06:00 and 14:30 UTC. QVPs were first used by Trömel et al (2014a) to reliably estimate backscatter differential phase, and Ryzhkov et al (2016) further expanded the QVP methodology and demonstrated its multiple benefits. The QVPs of polarimetric variables are obtained by azimuthal averaging of the radar data collected during conical PPIs at higher antenna elevation angles in order to reduce statistical errors of the variables and assign their average vertical profiles to a conical volume in a time-height display.…”
Section: Case 3: Riming/aggregation Processes Observed By Juxpolmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute these profiles, reflectivity and differential reflectivity measurements for each ray were averaged using range gates located within 1 km ground range of the measurement site. It should be noted that because of the availability of the range height indicator (RHI) scans, quasi‐vertical profiles [ Ryzhkov et al , ] were not used.…”
Section: Methodsmentioning
confidence: 99%
“…The use of quasi-VPR, when dealing with dual polarization radar variables, is a key aspect of this study. The term "quasi-VPR" actually refers to the fact that we are not looking at vertical radar observations but instead we derive vertical information by exploiting slanted paths [25]. In this study, quasi-VPRs are used to overcome the complication that would result if we attempted to perform QPEs using dual polarization estimators (i.e., using Z hh , Z dr , and K dp or a subset of them at the same time).…”
Section: Introductionmentioning
confidence: 99%